Indole-3-acetic acid promotes wound healing of potato tubers by activating auxin signaling and phenylpropanoid metabolism - Lirong Yu; Tongtong Cui; Pengdong Xie; Botao Bai; Ruirui Yang; Ye Han; Yi Wang; Xin Li; Yang Bi; Dov Prusky (Postharvest Biology and Technology, 2026)

Rapid aerobic sludge granulation by short-term in-situ chitosan dosing: Performance, mechanism and microbial response - Fengfan Yu; Ruirui Wang; Yanhang Wang; Mengjie Qian; Jintao Sun; Jinwen Song; Jinte Zou; Jun Li (Bioresource Technology, 2026)

Selective cleavage of Cβ-O-containing Cα-Cβ bond on Cu-Ni3S2 for electrocatalytic glycerol oxidation to formic acid - Ruirui Xu; Xinti Yu; Ce Fu; Lina Li; Zhangxing Chen; Heng Zhao (Chemical Engineering Journal, 2026)

N and S co-doped graphene-based single-atom catalysts for highly efficient nitrate reduction - Jin-Hang Liu; Yu Sun; Xiaoduo Jiang; Huixiong Jiang; Ruirui Wang; Yawei Wang; Huixian Ye; Xiudong Chen; Li-Ming Yang (Fuel, 2026)

Restorative coastal spaces: How spatial typologies and landscape elements shape psychological and physiological responses - Ruirui Zhu; Ruixin Xue; Yu Song; Jie Xiong; Ian Mell; Weijun Gao (Building and Environment, 2026)

Metabolic engineering of mannitol metabolism to improve protein production in Fusarium venenatum - Xizhen Liu; Longxue Ma; Ruirui Zhang; Yang Yang; Wuxi Chen; Liucheng Long; Yu Zheng; Demao Li (Systems Microbiology and Biomanufacturing, 2026)

Rhizosphere metabolic responses to soil acidification and their implications for nutrient uptake in eggplant - Tianqi Wang; Muhammad Awais; Xiaoyang Yu; Baiyi Bai; Zhen Wang; Ruirui Zhang; Lijie Yu; Dan Zhao; Xing Li; Ping Zhang; Roland Bol; Lijuan Yang (Rhizosphere, 2026)

Grazing Stocking Rate and Rainfall Jointly Regulate Soil Methane Uptake in a Temperate Meadow Steppe, but Do Not Reverse Net Methane Emissions - Tianqi Yu; Yu Zhang; Miao Wang; Chu Zhang; Jiquan Chen; Yuchun Yan; Xu Wang; Changliang Shao; Xiaotao Lü; Hui Li; Linghao Li; Lianhai Wu; et al. (Global Change Biology, 2026)
Grasslands are widely recognized as important sinks of methane (CH 4 ). However, their CH 4 uptake capacity has been increasingly weakened driven by human activities and changes in precipitation regimes. In particular, the rapid expansion of livestock grazing can lead to substantial increases in CH 4 emissions. For the Eurasian grasslands that have been subject to long‐term grazing, how well they currently function and will continue to function as CH 4 sinks under the changing precipitation regimes remains uncertain. Here we conducted an 11‐year grazing‐gradient experiment to assess the combined effects of grazing intensity and precipitation variability on grassland CH 4 fluxes. We measured soil CH 4 uptake in a manipulative grazing experiment in both wet and dry years, estimated livestock‐derived CH 4 emissions, and examined a range of biotic and abiotic drivers, including vegetation attributes, soil properties, and microbial biomass, for short‐ (prior to the onset of the lagged response) and long‐term (the entire experimental period) influences on the dynamics of CH 4 uptake in temperate meadow grasslands. Over the long term, CH 4 fluxes are jointly regulated by precipitation and grazing, with overgrazing amplifying the suppressive effect of rainfall on CH 4 uptake. Soil CH 4 uptake showed a lagged response to grazing, which may have been triggered by extreme rainfall events. While moderate grazing sustained the long‐term CH 4 uptake, it fails to offset livestock‐derived CH 4 emissions. In the short term, CH 4 fluxes are primarily governed by grazing, whereas in the long term they are jointly regulated by precipitation and grazing intensity. These results offer a new perspective for understanding the source–sink CH 4 dynamics of grasslands in the context of ongoing climate change.

Biomineralization induced by Shigella dysenteriae JS3: The mechanism, and the differences between biotic and abiotic whewellite and struvite - Na Guo; Jizheng Qiao; Shuhua Zhang; Shengzhe Gao; Yanhong Zhao; Chao Han; Hui Zhao; Yanyang Zhao; Xiao Gao; Ruirui Meng; Bin Cao; Yu Li; et al. (Chemical Geology, 2026)

Effective bioremoval of Cu (II) and Sulfate from acid mine drainage via biomineralization with an extreme acidophile bacterium V. pantothenticus WL - Chao Han; Xiangwei Cheng; Zuozhen Han; Shourui Dai; Qingyuan Chen; Wen Nie; Yu Han; Haibo Zhu; Xiao Gao; Yanyang Zhao; Fang Liu; Maurice E. Tucker; et al. (Journal of Contaminant Hydrology, 2026)

Mineralization of bacterial cells during proto-dolomite precipitation mediated by the halophilic bacteria Bacillus licheniformis - Ruirui Meng; Zuozhen Han; Wen Nie; Chao Han; Yu Han; Maurice E. Tucker (Chemical Geology, 2026)

mRNA Rather than Protein Expression of Hepatic Selenoprotein H is More Sensitive to Short-term Low Aflatoxin B1 Exposure in Mice with Varying Selenium Intake - Ruirui Yu; Mengru Hao; Aiping Liu; Chenggang Yang; Ping Xu; Yong Zhou; Alexey A. Tinkov; Aolin Yang; Qingqing Lv; Ziyu Han; Chao Wang; Zhou Wang; et al. (Biological Trace Element Research, 2026)

Dynamic simulation of fluoride leakage from power plant ash disposal sites and contamination risk to karst aquifers in semi-arid regions - Qing Wang; Yu Wang; Ruirui An (Journal of Contaminant Hydrology, 2026)

Degradation mechanism of diesel particulate emissions induced by non-thermal plasma - Yunxi Shi; Ruirui Ji; Xinyi Huang; Zhenguo Li; Jianbing Gao; Pan Wang; Jun Wang; Yixi Cai; Lei Yu (Journal of Environmental Chemical Engineering, 2025)

Bimetallic chloride in situ etching of NiFe alloy substrate to synthesize porous coral structure catalyst for efficient oxygen evolution reaction - Yu Zhang; Yaoxia Yang; Biaobiao Lu; RuiRui Zhang; Fuxing Zhou; Dongfei Sun; Qingtao Wang; Jian Li; Ziqiang Lei (Fuel, 2025)

Synthesis and biological evaluation of triazole alcohols containing an indole-3-methyl(phenyl)amino side chain against fluconazole-resistant Candida albicans - Zefei Fan; Lijiao Yang; Jidong Wang; Yafei Hou; Fei Zou; Tianyu Zhang; Yongyan Fu; Yue Zhang; Ruirui Wang; Shichong Yu; Guanghui Ni (Medicinal Chemistry Research, 2025)

Calcium and magnesium ions removal by different bacteria strains: Implications for limitation of lime-scale formation during seawater desalination - Ruirui Meng; Zuozhen Han; Wen Nie; Xiangwei Cheng; Chao Han; Yu Han; Maurice E. Tucker (Journal of Cleaner Production, 2025)

Light grazing tends to enhance ecosystem carbon sequestration and resource use efficiency in a meadow steppe of northern China - Hongliang Yu; Xu Wang; Yiqian Wu; Chongwei Wang; Ruirui Yan; Dawei Xu; Yuchun Yan; Xiaoping Xin (Agricultural and Forest Meteorology, 2025)

Assessment of the immune-developmental toxicity risk of the hygienic insecticide dimefluthrin in zebrafish (Danio rerio) model - Ruirui Li; Yang Yu; Wenxuan Cheng; Qingfeng Li; Wenping Xu; Jiagao Cheng; Liming Tao; Yang Zhang (Journal of Environmental Management, 2025)

Experimental study on the interaction of Sc-CO2 with feldspar and clay minerals: Implication for carbon sequestration in sandstone reservoirs - Yiming Luo; Mengting Xiao; Jianmei Cheng; Ying Yu; Fuqiao Xu; Ruirui Zhao; Kaisar Ahmat (Gas Science and Engineering, 2025)

A genomic compendium of cultivated food-derived lactic acid bacteria unveils their contributions to human health - Hao Jin; Keyu Quan; Lijun You; Lai-Yu Kwok; Teng Ma; Yalin Li; Xuan Shi; Xin Su; Ruirui Lv; Zhihong Sun; Wenjun Liu; Heping Zhang (Science Bulletin, 2025)

Muti-network active aerogel based on PVA, bacterial cellulose, and sodium alginate: Characterization, kinetics studies, and application for mutton preservation - Xi Zhou; Fangqu Wang; Yang Yu; Ruirui Guo; Xinran You; Xiaomei Xiang; Xiaojing Fan; Yabin Niu; Xuejiao Wang; Xianchao Feng; Lin Chen (Food Hydrocolloids, 2025)

The uptake and in-vivo migration of Hg by plants: a critical review - Xiaohan Chen; Ben Yu; Xuedong Wang; Ruirui Zhu; Lifei Zhang (Reviews in Environmental Science and Bio/Technology, 2025)

RAP1 is essential for PRRSV replication and the synthesis of the viral genome - Qiumei Wang; Heyou Yi; Anli Chen; Tao Tian; Zhiqing Yu; Lechen Lu; Ruirui Ye; Ermin Xie; Guoxin Zheng; Guihong Zhang; Heng Wang (Veterinary Microbiology, 2025)

Knocking Down HN1 Blocks Helicobacter pylori-Induced Malignant Phenotypes in Gastric Mucosal Cells and Inhibits Gastric Cancer Cell Proliferation, Cytoskeleton Remodeling, and Migration - Ying Huang; Xiaofei Wang; Hao Liu; Xiangkun Meng; Hua Yin; Ruirui Hou; Wan Lin; Xu Zhang; Jun Ma; Xiaoxu Zhang; Feixiong Zhang; Yu Miao (Biochemical Genetics, 2025)

Dissolved ammonia catalyzes proto-dolomite precipitation at Earth surface temperature - Ruirui Meng; Zuozhen Han; Xiao Gao; Yanyang Zhao; Chao Han; Yu Han; Renchao Yang; Shuangjian Li; Fang Liu; Maurice E. Tucker; Yanjing Chen (Earth and Planetary Science Letters, 2024)

Construction of foam-like carbon microspheres with controllable pseudo-graphitic domains: Synergistic enhancement of K-ion adsorption/intercalation storage - Qingjuan Ren; Lei Yan; Xuewen Yu; Wenhua Lei; Zhongyu Sun; Ruirui Hao; Jianzeng Yang; Zhiqiang Shi (Chemical Engineering Journal, 2024)

Coordination-regulated epitaxial growth for 2D/3D perovskite vertical alignment heterostructure - Guoxiang Zhao; Yuan Chen; Shan Cong; Lutao Li; Chen Wang; Xinyu Du; Ruirui Liu; Jing Lu; Yu Liu; Gaoyuan Chen; Sihan Zhang; Liya Zhang; et al. (Science Bulletin, 2024)

Screening and identification of reactive metabolic compounds of Cortex Periplocae based on glutathione capture-mass spectrometry - Guantong Yu; Ruirui Wang; Xiaomei Liu; Yuhong Li; Lin Li; Xiaoming Wang; Yuhong Huang; Guixiang Pan (Journal of Natural Medicines, 2024)

Suppressing lithium dendrite via hybrid interface layers for high performance quasi-solid-state lithium metal batteries - Bi Luo; Qi Wang; Weijie Ji; Guihui Yu; Zaowen Zhao; Ruirui Zhao; Bao Zhang; Xiaowei Wang; Jiafeng Zhang (Chemical Engineering Journal, 2024)

Thermal effects on rheological characteristics and its evolution mechanism of bio-modified rubberized asphalt for sustainable road system: A focus on rubber particle size - Tao Zhou; Lingwen Li; Ruirui Liu; Fangzhou Yu; Zejiao Dong (Journal of Cleaner Production, 2024)

Numerical simulation of CO2 storage by basalts in Xingouzui formation, Jianghan Basin, China - Ruirui Zhao; Zhi Zhong; Ying Yu; Rong Lü; Tingting Shi; Ningtao Wang; Jianmei Cheng (International Journal of Greenhouse Gas Control, 2024)

Unearthing the global patterns of cultural heritage microbiome for conservation - Yongjie Yu; Jianwei Zhang; Ruirui Chen; Claudia Coleine; Wenjing Liu; Manuel Delgado-Baquerizo; Youzhi Feng (International Biodeterioration & Biodegradation, 2024)

Environmentally relevant exposure to cotinine induces neurobehavioral toxicity in zebrafish (Danio rerio): A study using neurobehavioral and metabolomic approaches - Dan Yang; Wenfei Yu; Jiajia Qu; Yuexing Shen; Jingtong Yu; Ruirui Meng; Zhen Tao; Jiangfei Chen; Wei Du; Haitong Zhe Sun; Yunhui Zhang; Yuanchen Chen; et al. (Environmental Pollution, 2024)

Moderate grazing increased carbon, nitrogen and phosphorus storage in plants and soil in the Eurasian meadow steppe ecosystem - Miao Wang; Chu Zhang; Sisi Chen; Yu Zhang; Tianqi Yu; Xiaojuan Xue; Lianhai Wu; Wenneng Zhou; Xiangjun Yun; Ruirui Yan; Keyu Bai (Science of The Total Environment, 2024)

Identification of key factors affecting neonicotinoid residues in crops and risk of dietary exposure - Wenfei Yu; Ruxin Wu; Li Zhang; Yangzhong Pan; Jun Ling; Dan Yang; Jiajia Qu; Zhen Tao; Ruirui Meng; Yuexing Shen; Jingtong Yu; Nan Lin; et al. (Environmental Pollution, 2024)

Identification of point and nonpoint emission sources of neonicotinoid pollution in regional surface water - Yuanchen Chen; Jun Ling; Wenfei Yu; Li Zhang; Ruxin Wu; Dan Yang; Jiajia Qu; Hangbiao Jin; Zhen Tao; Yuexin Shen; Ruirui Meng; Jingtong Yu; et al. (Water Research, 2024)

How does grazing pressure affect feed intake and behavior of livestock in a meadow steppe in northern China and their coupling relationship - Tianqi Yu; Ruirui Yan; Chu Zhang; Sisi Chen; Zhitao Zhang; LeiFeng Guo; Tianci Hu; Chengxiang Jiang; Miao Wang; Keyu Bai; Wenneng Zhou; Lianhai Wu (Science of The Total Environment, 2024)

A large-scale comparative genomics study reveals niche-driven and within-sample intra-species functional diversification in Lacticaseibacillus rhamnosus - Lijun You; Ruirui Lv; Hao Jin; Teng Ma; Zhixin Zhao; Lai-Yu Kwok; Zhihong Sun (Food Research International, 2023)

Identification and expression profiles of candidate chemoreceptor genes in the tea leafhopper, Empoasca onukii Matsuda (Hemiptera: Cicadellidae) - Xiaoyue Lun; Xiuxiu Xu; Xinzhe Zhang; Yu Zhang; Ruirui Zhang; Yunhe Zhao; Zhengqun Zhang (Phytoparasitica, 2023)

Intraspecific microdiversity and ecological drivers of lactic acid bacteria in naturally fermented milk ecosystem - Lijun You; Hao Jin; Lai-Yu Kwok; Ruirui Lv; Zhixin Zhao; Menghe Bilige; Zhihong Sun; Wenjun Liu; Heping Zhang (Science Bulletin, 2023)

Hyaluronic acid modified oral drug delivery system with mucoadhesiveness and macrophage-targeting for colitis treatment - Ying Zhang; Ruirui Ma; Cuiyu You; Xue Leng; Danyang Wang; Shujing Deng; Binyang He; Ziyang Guo; Zelin Guan; Hengyu Lei; Jie Yu; Qinyuan Zhou; et al. (Carbohydrate Polymers, 2023)

Degradation of 2,4-Dichlorophenol Through Fenton Process Catalyzed by Nanoscale Zero-Valent Iron Supported by Biochar - Junlong Yu; Xiuxia Zhang; Ruojun Ma; Yi Du; Xiaodong Zhao; Shuai Zuo; Kangning Dong; Ruirui Wang; Yupeng Zhang; Yingying Gu; Juan Sun; Qiyou Liu (Water, Air, & Soil Pollution, 2023)

Root-derived C distribution drives N transport and transformation after 13C and 15 N labelling on paddy and upland soils - Xiaoting Wang; Ruirui Chen; Evangelos Petropoulos; Bingqian Yu; Xiangui Lin; Youzhi Feng (Biology and Fertility of Soils, 2023)

PCNA promotes PRRSV replication by increasing the synthesis of viral genome - Qiumei Wang; Heyou Yi; Yanchen Guo; Yankuo Sun; Zhiqing Yu; Lechen Lu; Ruirui Ye; Ermin Xie; Qianwen Wu; Yingwu Qiu; Weipeng Quan; Guihong Zhang; et al. (Veterinary Microbiology, 2023)

A novel protein domain is important for photosystem II complex assembly and photoautotrophic growth in angiosperms - Wei Li; Jiangfan Guo; Xue Han; Xiaowen Da; Kai Wang; Hongfei Zhao; Shi-Tang Huang; Bosheng Li; Hang He; Ruirui Jiang; Shichen Zhou; Peng Yan; et al. (Molecular Plant, 2023)

Heterogeneous Fenton oxidation of 2,4-dichlorophenol catalyzed by PEGylated nanoscale zero-valent iron supported by biochar - Junlong Yu; Xiuxia Zhang; Xiaodong Zhao; Ruojun Ma; Yi Du; Shuai Zuo; Kangning Dong; Ruirui Wang; Yupeng Zhang; Yingying Gu; Juan Sun (Environmental Science and Pollution Research, 2023)

Bioremediation of petroleum hydrocarbon contaminated soil by microorganisms immobilized on sludge modified by non-ionic surfactant - Junlong Yu; Ruyue Li; Xiuxia Zhang; Yi Du; Ruojun Ma; Xiaodong Zhao; Shuai Zuo; Kangning Dong; Ruirui Wang; Yupeng Zhang; Yingying Gu; Juan Sun (Environmental Science and Pollution Research, 2022)

sVCAM1 in the Hippocampus Contributes to Postoperative Cognitive Dysfunction in Mice by Inducing Microglial Activation Through the VLA-4 Receptor - Chenglong Li; Qi Li; Shuai Liu; Jiaying Li; Wei Yu; Yan Li; Ruirui Zhang; Sihua Qi (Molecular Neurobiology, 2022)

Effects of stocking rate on the interannual patterns of ecosystem biomass and soil nitrogen mineralization in a meadow steppe of northeast China - Yu Zhang; Jinling Zhao; Xiaoping Xin; Miao Wang; Fengjuan Pan; Ruirui Yan; Linghao Li (Plant and Soil, 2022)

Remote Sensing of the Coastline Variation of the Guangdong–Hongkong–Macao Greater Bay Area in the Past Four Decades - Ruirui Hu; Lijun Yao; Jing Yu; Pimao Chen; Dongliang Wang (Journal of Marine Science and Engineering, 2021)
In this study, a combination of example-based feature extraction and visual interpretation was applied to analyze the coastline variations in the Guangdong–Hong Kong–Macao Greater Bay Area (GHMGBA) from the past four decades based on the Landsat satellite remote sensing image data from 1987–2018, using ENVI and ArcGIS software. The results showed that the total length of the coastline of the GHMGBA increased in the past four decades, rising from 1291 km in 1987 to 1411 km in 2018. Among these, artificial coastline increased by 450 km, while the other coastline types decreased. The type of coastline that decreased the most was bedrock coastline, by a total of 172 km. The silty coastline disappeared, and almost all of it was converted to artificial coastline. Variations in the coastline of the GHMGBA were mainly connected to human activities and showed an overall trend of advancing towards the ocean. Dynamic monitoring of coastline variations can provide a reference for the protection of natural resources, sustainable marine development and rational planning of the coastal zone.

Adverse effects of short-term personal exposure to fine particulate matter on the lung function of patients with chronic obstructive pulmonary disease and asthma: a longitudinal panel study in Beijing, China - Ruirui Duan; Hongtao Niu; Tao Yu; Ke Huang; Han Cui; Chen Chen; Ting Yang; Chen Wang (Environmental Science and Pollution Research, 2021)

Response to Environmental Factors of Spawning Ground in the Pearl River Estuary, China - Dongliang Wang; Lijun Yao; Jing Yu; Pimao Chen; Ruirui Hu (Journal of Marine Science and Engineering, 2021)
Spawning grounds are important areas for fish survival and reproduction, and play a key role in the supplement of fishery resources. This study investigated environmental effects on the spatiotemporal variability of spawning ground in the Pearl River Estuary (PRE), China, using the generalized additive model (GAM), based on satellite remote sensing (sea surface temperature (SST), chlorophyll-a concentration (Chl-a), sea surface salinity (SSS), depth), and in situ observations. Results showed that 39.8% of the total variation in fish egg density was explained by these factors. Among them, the most important factor was SST, accounting for 14.3%, followed by Depth, SSS, and Chl-a, with contributions of 9.7%, 8.5%, and 7.3%, respectively. Spawning grounds in the PRE were mainly distributed in the waters with SST of 22 °C, depth of 30–50 m, SSS of 16–35 ‰, and Chl-a of 6–15 mg/m3. From spring to summer, the spawning ground moved from the outlet of the PRE to the east. The distribution of the spawning ground in the PRE was mainly affected by the Pearl River Plume (PRP), Guangdong Coastal Current (GCC), and monsoons in this area.

Design of supercontinuum laser hyperspectral light detection and ranging (LiDAR) (SCLaHS LiDAR) - Guoqing Zhou; Xiang Zhou; Youjian Song; Donghui Xie; Long Wang; Guangjian Yan; Minglie Hu; Bowen Liu; Weidong Shang; Chenghu Gong; Cheng Wang; Huaguo Huang; et al. (International Journal of Remote Sensing, 2021)

Analysis of pituitary transcriptomics indicates that lncRNAs are involved in the regulation of sheep estrus - Xiaoyue Li; Cunyuan Li; Yueren Xu; Rui Yao; Huixiang Li; Wei Ni; Renzhe Quan; Mengdan Zhang; Li Liu; Shuting Yu; Yaseen Ullah; Ruirui Hu; et al. (Functional & Integrative Genomics, 2020)

ABA signaling rather than ABA metabolism is involved in trehalose-induced drought tolerance in tomato plants - Wenqing Yu; Ruirui Zhao; Liu Wang; Shujuan Zhang; Rui Li; Jiping Sheng; Lin Shen (Planta, 2019)

Enhanced drought tolerance in tomato plants by overexpression of SlMAPK1 - Liu Wang; Ruirui Zhao; Rui Li; Wenqing Yu; Meijing Yang; Jiping Sheng; Lin Shen (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

The relationship between microvasculature in white matter hyperintensities and cognitive function - Jianzhong Sun; Xinfeng Yu; Yerfan Jiaerken; Ruirui Song; Peiyu Huang; Chao Wang; Lixia Yuan; Yingying Mao; Yang Guo; Hualiang Yu; Minming Zhang (Brain Imaging and Behavior, 2017)

Feasibility of human hair follicle-derived mesenchymal stem cells/CultiSpher®-G constructs in regenerative medicine - Pengdong Li; Feilin Liu; Chunling Wu; Wenyue Jiang; Guifang Zhao; Li Liu; Tingting Bai; Li Wang; Yixu Jiang; Lili Guo; Xiaojuan Qi; Junna Kou; et al. (Cell and Tissue Research, 2015)

Genome-wide identification and phylogenetic analysis of Family-1 UDP glycosyltransferases in maize (Zea mays) - Yanjie Li; Pan Li; Yong Wang; Ruirui Dong; Huimin Yu; Bingkai Hou (Planta, 2014)

Assessing ecological security at the watershed scale based on RS/GIS: a case study from the Hanjiang River Basin - Guangming Yu; Shu Zhang; Qiwu Yu; Yong Fan; Qun Zeng; Lei Wu; RuiRui Zhou; Na Nan; Pengjie Zhao (Stochastic Environmental Research and Risk Assessment, 2014)